Who gives for overseas development? - John Micklewright; Sylke Viola Schnepf (Institute for the Study of Labor (IZA), 2007)
Individuals' donations to overseas charities are an important source of funding for development assistance from rich industrialised countries. But little is known about the nature of these charitable donations. The literature on giving focuses on total donations to all causes and does not identify separately the pattern or the determinants of giving to any particular cause. We investigate giving to overseas causes using UK survey microdata that record individuals' donations to different types of charity. We establish a picture of overseas giving, comparing this with giving to other causes. Socio-economic correlates of both types of giving are analysed, including gender, marital status, occupation, education and, especially, income. We also investigate the relationship between individuals' overseas giving and their attitudes towards poverty in developing countries.
Keywords: 330; Charitable donations; overseas development; NGOs; Private Entwicklungshilfe; Spende; Großbritannien